HOW ENGLISH PRONUNCIATION AFFECTS COMMUNICATION - Murodulloyeva Feruza, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This research provides an extensive academic inquairy into the ontological metamorphosis of second language acquisition (SLA) through the integration of Artificial Intelligence (AI). It examines the transition from passive pedagogical tools to sophisticated neural-linguistic frameworks that act as "intelligent interlocutors." The study investigates how Large Language Models (LLMs) and algorithmic diagnostics minimize cognitive friction by providing real-time phonetic calibration and adaptive syntactic modeling. By synthesizing principles of computational linguistics with cognitive psychology, the article evaluates the synergy between machine precision and human emotional resonance. The research concludes that the mastery of AI-driven linguistic immersion represents the final frontier in achieving absolute communicative competence within the modern global discourse.